Beyond one-size-fits-all: Consumers react differently to packaging colors and names of cultured meat in Italy. (1st March 2023) - Califano, Giovanbattista; Furno, Marilena; Caracciolo, Francesco
Abstract: Cultured meat, also known as "in-vitro meat, " "clean meat, " "synthetic meat, " "lab-grown meat" and many other nomenclatures, represents one of the most recent controversial food technologies, even with its environmental benefits. Although the market success of cultured meat depends on consumers' acceptance, specific characteristics such as name and packaging color can influence consumers' perceptions and acceptance of the food product. This study assessed the impact of the name and packaging color of cultured meat on consumers' behavioral intentions toward its consumption in Italy. With the assumption that names and packaging colors affect consumers' acceptance differently, according to their characteristics and food neophobia, this study used a finite mixture model to analyze the stimulus impacts across different groups of consumers. The results showed that food neophobia plays a relevant role in individual response to name and packaging color of cultured meat. Less neophobic consumers are more likely to be positively affected in their intentions by green color packaging and nomenclatures that least emphasize the unnaturalness of the product, such as "clean meat, " whereas neophobic consumers are more likely to be positively affected only by green color.